Antiretroviral therapy effects on sources of cortical rhythms in HIV subjects: Responders vs. Mild Responders. Issue 1 (January 2015) - Babiloni, Claudio; Pennica, Alfredo; Vecchio, Fabrizio; Onorati, Paolo; Muratori, Chiara; Ferracuti, Stefano; Roma, Paolo; Donato, Nicole; Noce, Giuseppe; Del Percio, Claudio; Bonacci, Cristiano; Di Campli, Francesco; et al.
Highlights Five months of combined anti-retroviral therapy (cART) enhance biological and source electroencephalographic (EEG) markers in naïve HIV subjects. Enhancement of EEG source markers is greater in the naïve HIV Responders to the 5-month therapy (ΔCD4 > 100 cells/μl) than in Mild Responders (ΔCD4 < 100 cells/μl). The present EEG source markers may be used as secondary end points for pharmacological clinical trials in naïve HIV subjects.